Chitosan nano-formulation enhances stability and bactericidal activity of the lytic phage HK6 - Hasnaa R. Temsaah; Karim Abdelkader; Amr E. Ahmed; Nada Elgiddawy; Zienab E. Eldin; Hend Ali Elshebrawy; Nahed Gomaa Kasem; Fatma A. El-Gohary; Ahmed. F. Azmy (BMC Biotechnology)
Abstract Background Successful treatment of pathogenic bacteria like Enterobacter Cloacae with bacteriophage (phage) counteract some hindrance such as phage stability and immunological clearance. Our research is focused on the encapsulation of phage HK6 within chitosan nanoparticles. Result Encapsulation significantly improves stability, efficacy, and delivery of phages. Chitosan nanoparticles (CS-NPs) achieve a phage entrapment efficiency of 97%. Fourier-transform infrared spectroscopy (FT-IR) reveals shifts towards higher wavenumbers and a new peak, indicating amide bond formation and successful phage encapsulation. The average particle sizes for CS-NP and phage HK6 encapsulated CS-NPs were 180 ± 10 nm and 297 ± 18 nm, respectively. Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) analyses reveal that phage HK6 encapsulated CS-NPs are larger on average than CS-NPs, highlighting successful phage encapsulation. Encapsulated bacteriophages maintain its effectiveness at higher pH levels of 11 and 12. Both encapsulated and free bacteriophages are thermostable between 25 and 60 °C; while at higher temperatures (up to 80 °C), the encapsulated phage is thermally stable. Over four days, 70.57% of phages were released from encapsulated CS-NPs. Encapsulation of bacteriophage HK6 in CS-NPs enhances antibacterial activity within the first 2 h, compared to phage or nanoparticles alone. Conclusion This suggests that the phage HK6 encapsulated CS-NPs exhibit potentiality as biocontrol agents against resistant microorganisms offering an alternative to phage alone. Graphical Abstract